PENGARUH KECERDASAN SPIRITUAL DAN LINGKUNGAN SEKOLAH TERHADAP KECENRUNGAN SISWA BERPRILAKU BULLYING PADA SISWA SDN 001 TAMBUSAI KABUPATEN ROKAN HULU - Nilam Musdalifah; Zaka Hadikusuma Ramadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the influence of Spiritual Intelligence and the School Environment on the Tendency of Students to Behave in Bullying among Students at SDN 001 Tambusai, Rokan Hulu Regency. This research uses the variables Spiritual Intelligence and School Environment as independent variables and Students' Tendency to Behave in Bullying as the dependent variable. SDN 001 Tambusai. With a sample of 94 people using the total sampling method. The data analysis method used in this research is multiple linear regression technique. The results of this analysis show that Spiritual Intelligence and the School Environment influence the Tendency of Students to Behave in Bullying among Students at SDN 001 Tambusai, Rokan Hulu Regency. From the hypothesis test obtained, then the research hypothesis.